Effect of sodium oxide (Na2O) glass modifier on physical properties and gamma shielding in tellurite glass systems TeO2-ZnO-PbO-Bi2O3 (TZPB) - Marzuki, Ahmad; Ariyanti, Selvina; Alvyanti, Frisca Aulia; Kasy, Fransisca Indraningsih; Fausta, Devara Ega; Riyatun, Riyatun; Sari, Arum Luvita (Journal of Physics: Theories and Applications, 2023)
TZPB glasses with the composition 55TeO2-(41-x)ZnO-2Bi2O3-2PbO-xNa2O (x= 2; 2.5; 3; 3.5 mol%) have been fabricated and characterized to determine the physical properties and gamma radiation shielding parameters. The method of glass fabrication is melt quenching with the holding temperature at 900˚C for 30 minutes and the annealing temperature at 256˚C for 6 hours. The result of the characterization of the density and gamma shielding parameters was calculated using Phy-X PSD software. The glass density was measured using Archimedes's principle and showed a decrease from 5.79 to 5.73 g/cm3. The molar volume increased from 23.3 to 23.6 g/mol with the addition of Na2O concentration. Gamma radiation shielding parameters, LAC, MAC, MFP, HVL, and TVL simulated with the energy range were 10-3-105 MeV. The results of Phy-X/PSD software showed an increasing MAC, MFP, HVL, and TVL and decreasing in LAC with an increase in Na2O concentration.